Alasdair MacIntyre, George Lindbeck and the nature of tradition - Trenery, David (2014)
This thesis considers the question of justification of belief in a comprehensive metaphysical system, through an exposition and evaluation of the philosophy of Alasdair MacIntyre. It defines a comprehensive metaphysical system as a set of ontological and ethical presuppositions which are taken to encompass and explain the nature of the universe, and which provide a framework for human practical reasoning and action. The thesis argues that such a system is primarily a way of interpreting the world and the place of humanity within it, rather than a speculative theory. It considers the extent to which the notion of justification can be applied to such comprehensive systems, drawing on MacIntyre’s account of tradition-constituted rationality (TCR) and George Lindbeck’s account of religion as a cultural-linguistic system. It outlines the development of MacIntyre’s Aristotelian ethics and argues that the further development of that position in Dependent Rational Animals should be given a central role in the interpretation of his mature philosophy. The thesis illuminates the concept of TCR by applying Lindbeck’s rule theory of doctrine to the question of the identity of different traditions. The account of tradition that emerges from this exercise provides greater specificity to the concept of epistemological crisis, which is central to MacIntyre’s account of the superiority or inferiority of rival traditions. The account of superiority that emerges by linking MacIntyre and Lindbeck’s work provides a retrospective measure of the extent to which one tradition can be held to be (provisionally) justified or (absolutely) unjustified as a comprehensive metaphysical system, and provides a rebuttal to the claim that MacIntyre’s position is relativist. I argue that while Lindbeck’s original account of the nature of religion as a cultural-linguistic system is vulnerable to the charge of relativism, it can be strengthened against this claim by the incorporation of a notion of TCR derived from MacIntyre.